Impact of Brain derived Neurotrophic factor gene polymorphism on its peripheral levels in schizophrenic patients - Irshad Bibi; Farina Hanif; Quratulain Amir; Washdev Washdev; Mohammad Furqan Bari (Journal of the Pakistan Medical Association, 2024)
Objective: To determine serum levels of brain-derived neurotrophic factor and its polymorphism rs12291063 in schizophrenic patients. Method: The case-control study was conducted from January 1, 2020, to May 15, 2021, at Dr Abdul Qadeer Khan Institute of Behavioural Sciences, Dow University of Health Sciences, Karachi, and comprised schizophrenia cases aged 14-60 years who were diagnosed using Diagnostic and Statistical Manual of Mental Disorders-V criteria, and healthy controls without any psychiatric illness. Positive and negative syndrome scale score was used to assess disease severity. The genomic deoxyribonucleic acid of the subjects was isolated from peripheral blood, followed by polymerase chain reaction, gel electrophoresis and sequencing of the amplicons. The sequences were analysed using MEGA X software for genotyping. Serum brain-derived neurotrophic factor levels were assessed using enzyme-linked immunosorbent assay. Data was analysed using SPSS 21. Results: Of the 100 subjects, 50(50%) were cases; 36(72%) males and 14(28%) females (p<0.05) with mean age 34.34±10.32 years. There were 50(50%) controls; 32(64%) males and 18(36%) females (p=0.391) with mean age 30.886±8.88 years. Among the cases, the mean age at schizophrenia diagnosis was 25.14±9.54 years, and there was a significant association with positive family history for psychiatric disorders (p<0.05). Sequencing revealed no T>C substitution. Serum brain-derived neurotrophic factor levels were significantly higher in cases compared to controls (p<0.001). There was a weak negative correlation between brain-derived neurotrophic factor levels and positive and negative syndrome scale score (p<0.05). Conclusion: Higher brain-derived neurotrophic factor levels were found to be associated with schizophrenia, while no association of rs12291063 T>C was found with schizophrenia. Key Words: Brain derived neurotrphic factor, genotyping, Schizophrenia, Mental Disorders.